THE IMPLEMENTATION OF INDONESIAN NAVY VICTIM IDENTIFICATION POLICY IN LADOKGI R.E. MARTADINATA - Winarno, Sugeng; Sitam, Suhardjo; Hidayat, Bambang Hidayat; Subiyakto, Yuli (Journal of Indonesian Health Policy and Administration, 2020)
Soldier is a death-risk profession; thus, identification to have their exact identity is a fundamental right. The Presidential Regulation Number 107 of 2013 mandates Ladokgi RE. Martadinata as the investigator of victim identification activities for Indonesian Navy Soldiers. This study analyzes the implementation of the policy with a qualitative descriptive approach using the Edward III model analysis. Retrieval of primary informant data through in depth interviews and secondary data, including observation and review of the literature, documents, and related laws and regulations. Data validation is done by triangulating data sources, theories, and methodologies. The results of the study indicate that there are several supporting factors. First, the Ladokgi bureaucratic structure factor has a Military Dentistry Department in charge of managing dental antemortem data and had gathered 9000 soldiers data by 2019. The second is the resource factor. Ladokgi has regular budget sources from the state budget, personnel, health materials, and routine training programs. Third, the Ladokgi leadership's disposition factor has made the Navy Forensic Odontology into a functional organization under the control of the Ladokgi Chief. The fourth is communication factors, the existence of a tiered reporting system to the top command.However, there are several inhibiting factors. From the bureaucratic structure and resource factor is the absence of a root organization with various supporting professions for the identification. There is still the absence of standard information flow procedures in the reconciliation phase in the communication factor. In the disposition factor, the micro policy is absent in the form of guidelines for identifying victims in the Indonesian Navy. Conclusion. The implementation of the policy of identifying TNI AL casualties in Ladokgi RE. Martadinata has been implemented but is still partial, such as dental-based antemortem data management. We recommend that the commitment from the leader is needed in this case the Head of the Navy's Health Service regarding the involvement of required cross professional personnel in the organization of victim identification, through the revision of Presidential Regulation 107 of 2013 and the preparation of several technical policies needed in victim identification activities within the Navy.